Posted by Tracey on November 07, 2002 at 13:46:50:
In the example you give Solve 3x^2 + x - 2, when you factor it, I thought you had to find the multiple that would multiply out to equal -2 and add together to get x. I thought this would be (3x+2)(x-1)
Since -1 * 2 = -2 and 2 - 1 = 1 or in this case x. In the example you have this factored out to be
(3x - 2)(x + 1) = 0 -2 * 1 = -2 but -2 + 1 = -1 which would be -x. Shouldn't the x be positive? Am I wrong ? If so can you tell me where?
Post a Followup